Liquid Biopsy as a Source of Potential Biomarkers for Checkpoint Inhibitor Treatment in Non-Small Cell Lung Cancer - Kontić, Milica; Markovic, Filip (Medical Research, 2024)
Lung cancer (LC) is the leading cause of cancer-related mortality around the world. Immune checkpoint inhibitors (ICIs) have revolutionized treatment and improved clinical outcomes of non-small-cell lung cancer (NSCLC) patients. However, while some patients have good response to ICI others are refractory to therapy or have life threatening adverse reactions. There are still no good strategies to identify responders to ICIs. That is why personalization of ICI therapy based on patient’s unique genomic profile represents an attractive strategy to improve NSCLC treatment.There are continuous efforts to find predictive biomarkers to identify patients who are likely to respond to ICIs. In turn, these strategies are required to spare patients the time, expense, and toxicity of trying therapies from which they will not derive benefit. Based on this, non-invasive liquid biopsy has the potential to help identifying patients who may respond to ICI. Liquid biopsy derived circulatory tumor DNA, circulatory tumor cells, and immune cells-based biomarkers could be new biomarkers that will guide clinical decisions for checkpoint inhibitor treatment in NSCLC. Furthermore, these biomarkers can serve for monitoring the treatment response and unraveling the mechanisms of resistance.